COMPOSITION OF THE URALIDE CRUST FROM SEISMIC VELOCITY (VP, VS), HEAT FLOW, GRAVITY, AND MAGNETIC DATA - Brown D.; Carbonell R.; Ayala C.; Kukkonen I.; Golovanova I. (My University, 2003)
P-wave velocity (Vp), S-wave velocity (Vs), Poisson’s ratio (σ), heat flow, potential field, and surface geological data are integrated to constrain a model for the composition of the Uralide crust along the URSEIS transect. The model is constructed using published laboratory measurements of Vp, Vs, σ and density for a variety of crustal rock types. These laboratory data have been corrected for depth (pressure) and the Uralides temperature–depth function. The model shows clear differences between the composition of the old continental crustal nucleus of the East European Craton and the newly added crust of the accreted arc terranes to the east. The crust of the East European Craton is more felsic than that of the Magnitogorsk and East Uralian zones, and the latter two have a lowermost crust whose characteristics indicate a high garnet content (mafic garnet granulite) and/or the presence of hornblendite. The overall composition of the arc terranes is basaltic. Physical properties suggest that eclogite is not present in the arc terranes, or if present it exists in small amounts that are below the resolution of the data set. The lack of eclogite in the lower crust favours an intracrustal differentiation model for the evolution of the bulk composition of the continental crust. Nevertheless, the absence of surface uplift, the lack of metamorphism and late orogenic mantle melts, and the current crustal thickness indicate that crustal thinning did not affect the bulk composition of the Uralide crust.